A pilot study evaluating the safety and efficacy of En‐bloc holmium laser enucleation of the prostate in patients with a history of radiation therapy or high intensity focused ultrasound for management of organ confined prostate cancer with review of the literature - Renil S. Titus; Ansh Bhatia; Joao G. Porto; Jean C. Daher; Adele Raymo; Maggie Meyreles; Archan Khandekar; Aravindh Rathinam; Jonathan Katz; Robert Marcovich; Hemendra N. Shah (BJUI Compass, 2025)
Abstract Objectives To evaluate the safety and efficacy of Holmium Laser Enucleation of the Prostate (HoLEP) in managing patients with a history of organ‐preserving treatments (OPT: Radiation Therapy – RT, High Intensity Focused Ultrasound ‐ HIFU) for Organ‐Confined Prostate Cancer (OC‐PCa). Methods We reviewed men undergoing “en‐bloc” HoLEP between July 2017 and December 2023 from our institutional database to identify those with a history of OPT for OC‐PCa (study group). A 1:2 matched‐pair analysis was performed comparing these patients with a control group of men undergoing HoLEP for benign prostatic hyperplasia (BPH) without prior OPT. Demographic, perioperative and postoperative voiding parameters up to 1 year, as well as complications, were compared between groups. Unpaired t‐tests were used for parametric variables and Wilcoxon Rank tests for non‐parametric variables. A p‐value<0.05 was considered statistically significant. Results Of 660 patients, 15 had prior OPT before HoLEP. The time between OPT and HoLEP ranged from 3‐month to 12‐year. Associated urethral stricture and/or extensive prostatic calcification were present in five patients. Demographic and preoperative parameters were similar between the groups. However, the study group patient had significantly less resected tissue and higher rate of urinary incontinence at 3‐month. Two patients (13.3%) continued to experience incontinence at 1‐year. There was no clinically significant difference in postoperative improvement in voiding parameters amongst both groups. Conclusions HoLEP in patients with history of OPT for treatment of OC‐PCa is associated with a higher risk of transient urinary incontinence.